PARTISIPASI PEREMPUAN DALAM PEMILIHAN GUBERNUR PROVINSI LAMPUNG TAHUN 2008 - Yuswanto, Yuswanto (Faculty of Law, Universitas Jenderal Soedirman, 2011)
Lampung governor election on 2008 executed under article 233 (2) of act Number 32/2004 cencerning local government, on the other hand its implementation process is referred to act number 12 / 2008 concerning second ammendment of act number 32/2004 concerning local government. Governor election invites controversy both theoretically and practically. The research explores merely on the woman participation. Research method applies normative research that using secondary data deriving from primary, secondary and tertiary legal sources. The research shows that in governor election 2008 executed under article 233 (2) act number 32/2004 concerning local government and its implementation process based on act number 12/2008 , the fact show that from 5,36 milion voters, male voters reached of 2.778.763 voters, female was 2.587.978 voters, sehinso the total number was 5.366.741 voters. In sum, male voters was 51,77 %, and female voters was 48,33 %. This means that woman participation in governor election was 48,33 %. In another word, without woman participation, there is no one candidate can be stipulated as elected candidate. Keywords: governor election, woman participation